Category Reinterpretation and Defection: Modernism and Tradition in Italian Winemaking - Negro, Giacomo; Hannan, Michael T.; Rao, Hayagreeva (Organization Science, 2011)
When two groups of market actors differ in how to interpret a common label, each can make claims over the label. One categorical interpretation and the group that supports it risk disappearance if the rival interpretation gains ground. We argue that when members of the endangered category become partial defectors that span categories, their history presents challenges to the identity of nondefectors that will inhibit further change. Our empirical analysis of “traditionalism” and “modernism” in the making of Barolo and Barbaresco wines supports this argument.